2002
DOI: 10.1117/12.458418
|View full text |Cite
|
Sign up to set email alerts
|

<title>Advances in liquid crystal spatial light modulators</title>

Abstract: Recent advances in our high-speed analog liquid crystal spatial light modulators (SLMs) will be presented. These advancements include higher pixel density, smaller pixel pitch, greatly improved optical efficiency, and higher speed operation. The new VLSI SLMs can utilize ferroelectric liquid crystal (FLC) or nematic liquid crystal (NLC) to achieve phase-only, amplitude-only and phase-amplitude-coupled modulation. These devices have applications in optical processing, optical storage, holographic display and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Since liquid crystal spatial light modulators (SLMs) are currently the primary choice for digital holographic displays, it is quite relevant to briefly mention current capabilities of such devices. Bauchert et al [17] reported the desirable features of liquid crystal SLMs. These features can be summarized as higher number of pixels, smaller pixel period, better optical efficiency, and faster operation.…”
Section: A Overviewmentioning
confidence: 99%
“…Since liquid crystal spatial light modulators (SLMs) are currently the primary choice for digital holographic displays, it is quite relevant to briefly mention current capabilities of such devices. Bauchert et al [17] reported the desirable features of liquid crystal SLMs. These features can be summarized as higher number of pixels, smaller pixel period, better optical efficiency, and faster operation.…”
Section: A Overviewmentioning
confidence: 99%
“…Liquid crystal over silicon (LCoS) devices are a mature technology in the microdisplay market, offering various advantages over other technologies such as micromirrors [1,[3][4][5]. The main limitation with LCoS devices to date has been the response time of the liquid crystal, especially if gray-scale modulation is required.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial light modulators (SLMs) can be used to manipulate the polarization state, phase, or intensity of incident light, leading to many different applications [1]. In applications such as computergenerated holography and optical correlation, continuous phase modulation gives the most optically efficient usage of the light output by removing the 180°conjugate image as well as allowing more flexibility in the way the light can be manipulated [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, the spectral bandwidth limitation is imposed by the chromatic angular dispersion associated with diffraction. 5 Recent developments in high-pixel-number computer-addressable two-dimensional phase-modulating systems 6,7 create the opportunity to display high-resolution modulo-2π diffractive phase profiles. However, the practical application of diffractive wavefront control with discrete element addressing poses some unique challenges.…”
Section: Introductionmentioning
confidence: 99%